2004
DOI: 10.1130/g20805.1
|View full text |Cite
|
Sign up to set email alerts
|

New type of olivine fabric from deformation experiments at modest water content and low stress

Abstract: A new type of olivine fabric was found by high-strain simple-shear deformation experiments in the presence of trace amounts of water at ϳ0.5-2.2 GPa and ϳ1470-1570 K. In this fabric, called E-type fabric, the olivine [100] axis is subparallel to the shear direction, and the (001) plane is parallel to the shear plane; this geometry suggests that the [100](001) slip system makes the dominant contribution to total strain. This fabric is dominant at a modest water content, 200 Ͻ C OH Ͻ 1000 H/10 6 Si at low stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
216
1
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(235 citation statements)
references
References 22 publications
(26 reference statements)
14
216
1
4
Order By: Relevance
“…If, as we suggest, the peak temperature conditions in the Besshi unit developed at the same time as the tremolite in the Higashi- akaishi body then tremolite should occur only close to or at higher grades than the oligoclase-biotite zone. An inspection of the geographic distribution of the metamorphic zones [Enami, 1982] and the presence of tremolite shows an excellent agreement (Figure 8b) suggest that D 1 took place under low water activities at relatively high-temperature conditions [Katayama et al, 2004;Nicolas and Christensen, 1987]. 6.1.1.…”
Section: P-t Conditions For Tremolite Formationmentioning
confidence: 95%
“…If, as we suggest, the peak temperature conditions in the Besshi unit developed at the same time as the tremolite in the Higashi- akaishi body then tremolite should occur only close to or at higher grades than the oligoclase-biotite zone. An inspection of the geographic distribution of the metamorphic zones [Enami, 1982] and the presence of tremolite shows an excellent agreement (Figure 8b) suggest that D 1 took place under low water activities at relatively high-temperature conditions [Katayama et al, 2004;Nicolas and Christensen, 1987]. 6.1.1.…”
Section: P-t Conditions For Tremolite Formationmentioning
confidence: 95%
“…Studies by Katayama et al (2004), Jung et al (2006), and Katayama and Karato (2006) mapped out the occurrence of Surv Geophys (2009) 30:407-461 429 five different olivine fabric types (the original A-type plus B-, C-, D-, and E-types). Karato et al (2008) suggested that that the asthenospheric upper mantle may generally be dominated by E-or C-type olivine rather than the traditionally assumed A-type.…”
Section: The Upper Mantlementioning
confidence: 99%
“…Based on high pressure deformation experiments, Karato and co-workers have proposed a classification in five types of olivine fabrics developing as a function of the applied stress and water content (Jung and Karato, 2001), but until now, the physical mechanism which could explain the crystallographic preferred orientations (CPO) variations is still lacking. Other studies recognized an effect of grain size on the strength of olivine (Goetze, 1978;Karato et al, 1986;Karato and Wu, 1993;Katayama et al, 2004). At smaller grain sizes (sub µm), dislocations are increasingly captured by grain boundaries, resulting in only few organized sub grain boundaries.…”
mentioning
confidence: 99%